Peran Kepolisian Dalam Menangani Kekerasan Dalam Rumah Tangga (KDRT) - Situmorang, Eka Irma; Neri Widya Ramailis (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the role of the police in handling domestic violence (DV) in the jurisdiction of the Pekanbaru Police. This study uses a qualitative method with a descriptive approach, data collection techniques through observation, in-depth interviews, and documentation. The results of the study indicate that the police play a central role in the process of handling DV cases, from receiving reports, protecting victims, conducting investigations, to mediation and law enforcement. This study recommends enhancing the capacity and sensitivity of police officers, fostering inter-sectoral collaboration, and providing legal education to the community to create a more responsive environment and protect DV victims in the city of Pekanbaru. The conclusion of this study indicates that the role of the police is crucial in handling domestic violence in Pekanbaru, both through legal (penal) and non-legal (non-penal) approaches; however, its effectiveness still needs to be improved through personnel training, cross-sectoral collaboration, and continuous community education. Keywords: Domestic Violence, Pekanbaru Police Station, Role of Police.